(untitled) (Eurasian Research Bulletin, 2024)
This article aims to ensure the effectiveness of the tax and budget system in the new development strategy in the country. Also, the formulas for calculating the tax potential from the property of individuals, in addition to improving the tax policy, improving the development of existing innovative methods and methodological approaches in determining budget needs, and the main aspects of equalization programs, by using complex methods of economic and taxation, local governments can potentially increase their revenue streams, which can then be explored for various public services, infrastructure projects or other community needs. This example provides suggestions for adapting and improving fiscal policy to address local economic priorities and challenges